Internet connectivity disruption in Kazakhstan (Kazakhstan) - Voidly (2026)
CRITICAL severity mixed detected in Kazakhstan. Confidence: 75%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KZ-2026-0078
Keywords: censorship; KZ; mixed; critical